Utilización de suero ácido de leche y extracto de Rábano ((raphanus sativus var. longipinnatus) en el reemplazo de nitritos en la producción de un embutido de pasta fina tipo Mortadela - Agualongo Orozco, Brayan Antonio (2019)
Processed meat products have been classified as possible carcinogens due to their extensive consumption according to the World Health Organization (WHO), due to the nitrated salts of synthetic origin used in cured meat products, however, nitrated salts give sensory characteristics to the product and they help to conserve microbiology by reducing the growth of Salmonella, Clostridium botulinum spp, Escherichia Coli and Listeria monocytogenes. Therefore, the objective of the project was to apply a vegetable extract of radish (ER) as a source of nitrates in combination of acid whey (SA) for the preparation of a sausage of fine pasta type mortadella. The preservative effect was evaluated by means of the variable responses of colorimetry, pH, microbiology of the product (Escherichia Coli and Listeria monocytogenes), sensory characteristics and shelf life (TVU). Two types of liquid and powder extract were formulated, two concentrations of acid whey at 4 and 5% and two types of incubation and unincubation methods as indicated: Control (125 ppm nitrate), t1 (ER L + SA 4 % + SI), t2 (ER L + SA 4% + NO), t3 (ER L + SA 5% + SI), t4 (ER L + SA 5% + NO), t5 (ER P + SA 4% + SI), t6 (ER P + SA 4% + NO), t7 (ER P + SA 5% + SI) t8 (ER P + SA 5% + NO). Additionally, the effect of time during 14 days of rest under refrigeration conditions at 4 ° C was analyzed to favor the development of the reactions that influence the characteristics of the final product.